Respons Hidrasi Atlet Pencak Silat terhadap Konsumsi Minuman Susu Rekonstitusi: Respons Hidrasi Atlet Pencak Silat terhadap Konsumsi Minuman Susu Rekonstitusi - Alina Hizni; Samuel; Sholichin (Amerta Nutrition, 2026)
Background: Stunting is considered a chronic nutritional problem with serious impacts. In 2021, SSGI reported a 24.4% prevalence of stunting in East Nusa Tenggara, with South Central Timor (48.3%) experiencing the highest cases. Stunting causes are multifactorial, influenced by inadequate nutrition, sociodemographic factors, and paternal roles affecting parenting and infection susceptibility. Objectives: This study aims to determine the risk factors for stunting according to sociodemographic characteristics and fathers' role in the South Central Timor Regency. Methods: A cross-sectional quantitative design was used, including 280 respondents selected through purposive sampling. Inclusion criteria were children aged 6–59 months residing in Noesiu and Tobu Villages, possessing a Child Health Card (KIA), and providing informed consent. Exclusion criteria were families of stunted children who were absent or had relocated. Data were obtained through interviews, observations, anthropometric measurements, and secondary sources. Logistic regression was used for both bivariate and multivariate analyses. Furthermore, variables with p-values<0.25 in the bivariate stage were incorporated into the final model. The Kupang Health Polytechnic's Health Research Ethics Committee provided the ethical permission (No. LB.02.03/1/0156/2024). Results: Stunting was found to be significantly associated with low birth weight, exclusive breastfeeding, a history of infectious diseases, mothers' nutritional status (chronic energy deficiencies), and paternal role (p-value<0.05). Multivariate analysis identified maternal nutritional status and exclusive breastfeeding as the most influential factors. Conclusions: Maternal nutritional status and low rates of exclusive breastfeeding were identified as major risk factors for stunting. Further studies should include variables such as immunization status, smoking habits, and diet.